Analyzing Determinants of Islamic Stock Market Performance in Indonesia and Malaysia - Kafabih, An’im (International Journal of Economics, Management and Accounting, 2025)
Indonesia has higher volatility in Islamic stock market compared to Malaysia. As volatility of each market is derived from its Islamic stock performance, the goal of this paper is to analyze determinant factors of Islamic stock market performance in Indonesia and Malaysia. Using inflation and exchange rate as monetary policy objectives (MPO) and VIX (investors fear and market volatility), and gold price as global indicators for independent variables, ARDL bound test is performed with monthly Indonesia and Malaysia data. Indonesia data are gathered from December 1994 to February 2023, whereas Malaysia data are from January 2010 to February 2023. The results show that inflation and exchange rate become the main driving force of Islamic stock market performance in Indonesia in the long run, while the exchange rate is true for Malaysia. In the short run, inflation become the driving factor of Islamic stock performance in Indonesia and Malaysia. This paper also finds that gold investment able to become safe-haven asset in Indonesia in short and long run, while in Malaysia gold investment can be a safe-haven asset in the short run only. This paper also finds that VIX do not have any significant result only in Indonesia in short run. Implication of these results are the essential role of Central bank of Indonesia to achieve its inflation targeting, and the important role to rise capital gain tax.